2020
DOI: 10.1038/s41598-020-79043-1
|View full text |Cite
|
Sign up to set email alerts
|

Acid resistance of Masson pine (Pinus massoniana Lamb.) families and their root morphology and physiological response to simulated acid deposition

Abstract: Pinus massoniana Lamb. is one of the most sensitive species to acid deposition among forest woody plants, but differences in acid resistance among pine families still exist. It is of great significance to study the differences in acid resistance of Masson pine families and to analyze the physiological regulation mechanism of their acid resistance. In this study, the 100-day-old seedlings of 16 Masson pine families were treated with the simulated acid rain (SAR) at different pH levels (5.6, 4.5, 3.5 and 2.5) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Direct, indirect, and total impact tables of AR pH and NO 3 − concentrations on height growth rate and basal diameter growth rate of Q. acutissima and C. lanceolata saplings This table shows the standardized direct, indirect, and total effects of the concentration of NO 3 − in AR and AR pH on the height and basal diameter growth rates of Q. acutissima and C. lanceolata saplings Various plants have different tolerances for AR(Ren et al 2018), and studies have found that the abundance of H + caused by AR is the main factor that threatens the growth of trees. The trees absorb H + into plant cells through roots, which induces changes in intracellular free radicals that have adverse effects on root growth(Zhou et al 2020). Consistent with the above results, redundancy analysis and structural equation modeling showed that AR pH had a positive standardized total effect on growth rates of Q. acutissima and C. lanceolata (the higher the acidity of the AR, the greater the negative impact).…”
supporting
confidence: 71%
“…Direct, indirect, and total impact tables of AR pH and NO 3 − concentrations on height growth rate and basal diameter growth rate of Q. acutissima and C. lanceolata saplings This table shows the standardized direct, indirect, and total effects of the concentration of NO 3 − in AR and AR pH on the height and basal diameter growth rates of Q. acutissima and C. lanceolata saplings Various plants have different tolerances for AR(Ren et al 2018), and studies have found that the abundance of H + caused by AR is the main factor that threatens the growth of trees. The trees absorb H + into plant cells through roots, which induces changes in intracellular free radicals that have adverse effects on root growth(Zhou et al 2020). Consistent with the above results, redundancy analysis and structural equation modeling showed that AR pH had a positive standardized total effect on growth rates of Q. acutissima and C. lanceolata (the higher the acidity of the AR, the greater the negative impact).…”
supporting
confidence: 71%
“…However, no significant difference was found in soil pH between treatments at pH 4.5, 5.5, and 7.0. Similarly, Zhou et al (2020) found that SAR caused a lowering of both rhizosphere and non-rhizosphere soil pH with the decrease of SAR pH in Masson pine (Pinus massoniana) seedlings. Wei et al (2020) also showed that SAR of pH 5.5, 4.5, 3.5, and 2.5 reduced the soil pH by 5.1, 6.8, and 7.0% in latosols, lateritic red soils, and red soils, respectively.…”
Section: Effects Of Acid Rain On Soilmentioning
confidence: 90%
“…Mineral nutrients particularly Ca and Mg increased plants' resistance to AR (Diatta et al 2021). Zhou et al (2020) found that SAR of pH 2.5 and 3.5 severely damaged the root plasma membrane (PM) permeability in Masson pine (Pinus massoniana) seedlings, while pH 4.5 and 5.6 lowered the PM permeability, thus indicating that SAR can destroy the integrity of plant PM.…”
Section: Physiological and Biochemical Performancesmentioning
confidence: 99%
“…This disruption manifests in reduced root systems, altered root morphology, and, in extreme cases, root tip death, ultimately culminating in plant mortality. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%